Waterborne polyurethanes prepared from benzophenone derivatives with delayed fluorescence and room-temperature phosphorescence. Issue 11 (20th February 2018) - Wang, Tao; Zhou, Cao; Zhang, Xingyuan; Xu, Dong
Abstract : Charge-transfer states serve as a bridge between singlet and triplet states and polymerization can further promote communication between them. Abstract : Dual-emissive materials with both fluorescence and room-temperature phosphorescence (RTP) are extensively used in bioimaging, sensors, and optoelectronics. Here, a series of N, N -substituted benzophenone-based waterborne polyurethanes (WPUs) were synthesized by a facile polycondensation reaction, which exhibit both delayed fluorescence (DF) and RTP emission utilizing strong intramolecular charge-transfer states (CT states) to serve as a bridge between singlet and triplet states. The basic structural and luminescent characterization is mainly investigated. With an increase in dye loadings, there is a progressive mergence between the singlet and triplet states, which can be explained by polymerization-enhancing intersystem crossing (PEX), a model based on Kasha's molecular exciton theory, leading to tunable fluorescence and RTP. As a result, by a rational design it could be a common method to develop single-component luminescent materials with both fluorescence and RTP.